1993
DOI: 10.1111/j.1365-2958.1993.tb01114.x
|View full text |Cite
|
Sign up to set email alerts
|

Basement membrane carbohydrate as a target for bacterial adhesion: binding of type I fimbriae of Salmonella enterica and Escherichia coli to laminin

Abstract: Adherence of type-1-fimbriate Salmonella enterica and Escherichia coli to immobilized proteins of the extracellular matrix and reconstituted basement membranes was studied. The type-1-fimbriate strain SH401 of S. enterica serovar Enteritidis showed good adherence to laminin, whereas the adherence to fibronectin, type I, type III, type IV or type V collagens was poor. Only minimal adherence to the matrix proteins was seen with a non-fimbriate strain of S. enterica serovar Typhimurium. A specific and mannoside-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
104
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 55 publications
3
104
0
Order By: Relevance
“…These finding is in agreement with earlier reports by Huguette et al (1996), Alaa and Adnan (2011) which both found that the fimA gene contains sequences unique to Salmonella isolates and demonstrated that this gene is suitable for PCR target for the detection of Salmonella strains. Bacterial adherence (Kurkkonen et al, 1993) is considered to be a baseline requirement for infection, and there is evidence that many bacteria have surface appendages, such as pili or fimbriae (Clegg et al, 1985;Aslanzadeh and Paulissen, 1992), that facilitate their binding to specific receptors on the epithelial cell surface, or intestinal mucus. Although certain types of Escherichia coli fimbriae are known to be important for virulence, only type 1 fimbriae (fimA) have been implicated in Salmonella pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These finding is in agreement with earlier reports by Huguette et al (1996), Alaa and Adnan (2011) which both found that the fimA gene contains sequences unique to Salmonella isolates and demonstrated that this gene is suitable for PCR target for the detection of Salmonella strains. Bacterial adherence (Kurkkonen et al, 1993) is considered to be a baseline requirement for infection, and there is evidence that many bacteria have surface appendages, such as pili or fimbriae (Clegg et al, 1985;Aslanzadeh and Paulissen, 1992), that facilitate their binding to specific receptors on the epithelial cell surface, or intestinal mucus. Although certain types of Escherichia coli fimbriae are known to be important for virulence, only type 1 fimbriae (fimA) have been implicated in Salmonella pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Others play pivotal roles in the survival of organism in the host system-mgtC (Magnesium transport C) (Blanc-Potard and Groisman 1997) or in the actual manifestation of pathogenic processes for example stn (Salmonella toxin), pip A, B, D (Marcus et al, 2000). Bacterial adherence (Kurkkonen et al, 1993) is considered to be a prerequisite for infection, and there are evidences that many bacteria have surface processes, such as fimbriae (Clegg et al, 1985;Aslanzadeh and Paulissen, 1992) or pili, that facilitate attachment to particular receptors on the epithelial cell surface, to urinary tract or intestinal mucus. Although certain strains of E. coli fimbriae are known to be important for virulence, only type 1 fimbriae (fimA) have been implicated in Salmonella pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Several glycosylated receptors for type 1 pili have been documented, such as glycosylphosphatidylinositol-anchored (GPI-anchored) protein CD48, Tamm-Horsfall protein (THP), and various family members of carcinoembryonic antigen-related cell adhesion molecules (CEACAMs) (16)(17)(18)(19)(20). Western blot analysis of total protein extract from ileal specimens of 9 CD patients, taken in both involved and uninvolved areas, and of 9 controls showed a strong expression of CEACAM5 (also called CEA or CD66e) and CEACAM6 (also called CD66c or non-crossreacting antigen [NCA]) in the ileal mucosa of CD patients in both involved and uninvolved areas ( Figure 3A).…”
Section: Introductionmentioning
confidence: 99%
“…However [19]. The SEF17 fimbrial structure, which was demonstrated to share 70°% identity with the 'curli' fimbrial structure of E. coli [20], generated an aggregative phenotype and bound fibronectin [21][22][23].…”
Section: Introductionmentioning
confidence: 99%